Study protocol: Transition from localized low back pain to chronic widespread pain in general practice: Identification of risk factors, preventive factors and key elements for treatment – A cohort study - Viniol Annika; Jegan Nikita; Leonhardt Corinna; Strauch Konstantin; Brugger Markus; Barth Jürgen; Baum Erika; Becker Annette (BMC Musculoskeletal Disorders, 2012)
Abstract Background Chronic localized pain syndromes, especially chronic low back pain (CLBP), are common reasons for consultation in general practice. In some cases chronic localized pain syndromes can appear in combination with chronic widespread pain (CWP). Numerous studies have shown a strong association between CWP and several physical and psychological factors. These studies are population-based cross-sectional and do not allow for assessing chronology. There are very few prospective studies that explore the predictors for the onset of CWP, where the main focus is identifying risk factors for the CWP incidence. Until now there have been no studies focusing on preventive factors keeping patients from developing CWP. Our aim is to perform a cross sectional study on the epidemiology of CLBP and CWP in general practice and to look for distinctive features regarding resources like resilience, self-efficacy and coping strategies. A subsequent cohort study is designed to identify the risk and protective factors of pain generalization (development of CWP) in primary care for CLBP patients. Methods/Design Fifty-nine general practitioners recruit consecutively, during a 5 month period, all patients who are consulting their family doctor because of chronic low back pain (where the pain is lasted for 3 months). Patients are asked to fill out a questionnaire on pain anamnesis, pain-perception, co-morbidities, therapy course, medication, socio demographic data and psychosomatic symptoms. We assess resilience, coping resources, stress management and self-efficacy as potential protective factors for pain generalization. Furthermore, we raise risk factors for pain generalization like anxiety, depression, trauma and critical life events. During a twelve months follow up period a cohort of CLBP patients without CWP will be screened on a regular basis (3 monthly) for pain generalization (outcome: incident CWP). Discussion This cohort study will be the largest study which prospectively analyzes predictors for transition from CLBP to CWP in primary care setting. In contrast to the typically researched risk factors, which increase the probability of pain generalization, this study also focus intensively on protective factors, which decrease the probability of pain generalization. Trial registration German Clinical Trial Register DRKS00003123